Development of human enterovirus 71 nano calcium phosphate adjuvanted candidate vaccine for parenteral and mucosal delivery - Saeed Ahmed, Mohamed Ibrahim (2015)
A successful potent vaccine for protection against the faecal-oral pathogen human Enterovirus 71, requires the induction of both parenteral and mucosal immunity concurrently. Adsorbing the vaccine to a nano-sized particulate adjuvant will boost the systemic immune response towards parenteral administrated vaccine, and combining the vaccine adjuvant and delivery carrier in one formulation for delivering mucosal vaccines is expected to improve the post-vaccination HEV71 mucosal protection. The purpose of this work was to examine the applicability of inducing improved postvaccination immunity of Human Enterovirus 71 killed vaccine based on using nanosized vaccine-adjuvant particles, variable routes of parenteral immunization and different polymeric delivery carriers for inducing enhanced post vaccination immunity as a novel approach for the development of an effective HEV71 vaccine. A novel in vitro delivery system was designed and used to examine the in vitro release of the HEV71 killed-virus and calcium phosphate (CaP) adjuvants from the encapsulating delivery carrier comprising nano-sized chitosan and micro-sized alginate hydrogels prepared and used to compare their in vitro capacity of releasing the vaccine and adjuvant using commercial HEV71-VP1 kit and a Calcium Calorimetric Quantification Kit. In addition, an intervention animal study was conducted on laboratory experimental rabbits to examine its capacity for inducing post-vaccination systemic IgG levels from HEV71 killed-virus adsorbed in nano- and micro-sized CaPadjuvants through intradermal and intramuscular routes. Buccal delivery consisted of HEV71 killed-virus adsorbed with CaP-adjuvant encapsulated in chitosan and alginate hydrogels and with the unvaccinated group kept as a control. The animals were immunized with HEV71 vaccine formulation and blood samples were withdrawn at 0, 1, 3, 5 and 7 weeks post immunization, the last samples were collected two weeks after the last dose. The samples were examined for the presence of HEV71 specific IgG and IgA antibody classes in the serum and saliva using an in-house developed ELISA assay. The in vitro delivery of adjuvant loaded polymeric carrier offered an improved and sustained release of the nano-adjuvant encapsulated in chitosan but not alginate, due to the reversibility of adjuvant-polymer interaction. Moreover, chitosan hydrogel showed better encapsulation and reversible interaction with both the nano- and micro-sized adjuvant particles. The in vitro delivery of HEV71 killed-virus adsorbed adjuvant loaded onto a polymeric carrier displayed a superior capacity for generating an optimized sustained release of vaccine epitopes. Chitosan loaded nano-adjuvant offered ascending and extended vaccine antigen release, due to its smaller adjuvant size and reversibility of interaction, but not in alginate-adjuvant formulations, due the vaccine been sequestered in the calcium-alginate chemical crosslink. In immunized animals, the nano-CaP in a one-tenth millilitre intradermal dose induced a higher level of viral specific antibody levels, which was almost equal to the intramuscular one millilitre administered after five doses. The nano-sized CaP was capable of producing a higher level of viral specific antibodies compared to the microparticle sized commercial adjuvant or the vaccine without adjuvant when administered through the intradermal route. Intramuscular immunization with either nano- or microparticles CaP adsorbed HEV71 killed-virus was able to induce higher viral specific antibodies than the nano-CaP adsorbed vaccine alone. Chitosan encapsulation of the vaccine or a vaccine with nano-CaP induced a high IgA level due to its extended swelling, and reversibility of releasing the vaccine. The alginate formulations had no effect on the IgA levels, it seems the vaccine epitopes were trapped in the alginate composite. The effect of joint dual immunization parenteral and mucosal routes (nano-CaP-HEV71 killed-virus (ID) and vaccine encapsulated in chitosan through the buccal delivery) to the same animals induced enhanced both types of systemic and mucosal antibody responses, as displayed in serum IgG and salivary IgA antibody levels towards the vaccine. The vaccine being adsorbed into the nano-CaP (intradermal) offered enhanced virus neutralization in animal serum samples. However, the enhancement of the virus neutralization in saliva, seemed to be hindered by the flow of the salivary secretion. In conclusion, the application of a novel nano-sized calcium phosphate as adjuvant is a promising strategic approach for the development of an improved HEV71 postvaccination parenteral immunity. In addition, polymeric carrier concentration, hydrogel swelling capacity, the nature of adjuvant-carrier interaction, are important factors for the sustained release process of CaP-adjuvant and HEV71 killed-virus on the novel created vaccine delivery model. The use of a nano-sized adjuvant encapsulated in a muco-adhesive carrier introduces a novel system for the enhancement of post vaccination mucosal immunity not only through the buccal mucosa, but also to the other mucosal surfaces, such as nasal or urogenital. Furthermore, the joint vaccine administration through the parenteral and mucosal routes enhanced the level of secretory IgA antibody in the saliva. In addition, an elevated post vaccination humoral immune response of a highly specific IgG and neutralizing antibodies was as shown in the in vitro inhibition of HEV71 live virus infectivity to Vero cell at the highest sample dilutions. Finally, the study finding is a key indicator for the role of nano-size adjuvant and carriers in augmenting the postvaccination immunity. This could be applied to improve the post-vaccination immunity against other medical pathogens without limiting to Human Enterovirus 71.